Cross Talk Between Ferroptosis and Cerebral Ischemia - She, Xu; Lan, Bin; Tian, Haomei; Tang, Biao (Frontiers in Neuroscience, 2020)
Recently, ferroptosis has been presented as a new form of regulated cell death. Differ from apoptosis or necrosis, ferroptosis is driven by iron-dependent lipid peroxidation. The metabolism of iron, lipid and amino acid plays a significantly regulatory role in ferroptosis, which can be reversed by glutathione peroxidase 4 (GPX4) and ferroptosis suppressor protein 1 (FSP1). Ferroptosis is implicated in the onset and development of numerous neurological diseases. Emerging studies have revealed that ferroptosis was evoked and in return aggravated damage of brain tissue following cerebral ischemia, while inhibition of ferroptosis could dramatically attenuate the damage. In this review, we summarized the mechanistic relationship between ferroptosis and cerebral ischemia: iron overload, down-regulation of GPX4 and up-regulation of lipid peroxidation. Admittedly, the researches on ferroptosis involved cerebral ischemia have paid much attention to the effect of ferroptosis to cerebral ischemia injury. However, the specific mechanism remains to further verify through experiment, including how cerebral ischemia induces ferroptosis and how ferroptosis deteriorates cerebral ischemia.